DEFECATION POSTURE – SITTING VERSUS SQUATTING - Grzegorz Zalewski,; Mateusz Myśliwiec,; Maciej Karwat,; Dominik Sendecki,; Julia Kular,; Oliwia Malec,; Justyna Niebylecka,; Izabella Michalska,; Natalia Glanc,; Tytus Tyralik, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Despite emerging debates on what should constitute a recommended defecation posture the research in this area has been mostly non-conclusive. In the countries of Europe, America, Australia the sitting position forced by a design of water toilet prevails while in many Asia and Africa countries the squatting posture dominates. The postures have their distinctive impact on digestive, musculoskeletal, and overall body health. Both of them have advantages  and disadvantages.Aim: This systematic review aimed to critically evaluate previous research on the defecation posture. The comparison of changing the defecation position from squatting to sitting was performed and its effects analysed.Material and methods: A search of relevant research databases was conducted as well as a hand search of selected journals to identify eligible papers.Results: A total of 20 studies were reviewed and results indicated a mean prevalence rate of sitting posture between 10%–24%. Findings also indicated correlates such as the presence of health problems related to the defecation posture. Most studies showed poor external validity, with the majority of them scoring high on risk of bias.Conclusions: Overall, the findings indicate inconsistencies in terms of methodology and diagnostic criteria of health problems related to defecation posture. Further research in this area using long-term clinical trials to avoid biases is recommended.